XÁC ĐỊNH GIỚI HẠN VÀ ĐÁNH GIÁ HIỆU QUẢ XỬ LÝ NƯỚC MẶT CỦA VIÊN XỬ LÝ NƯỚC DG19 TRONG ĐIỀU KIỆN DÃ NGOẠI - Võ, Thị Hoài Thu; Hoàng, Quang Cường; Đinh, Thị Thu Trang; Lê, Thị Huệ; Nguyễn, Công Tỉnh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
LIMITS DETERMINATION AND EFFECTIVE ASSESSMENT OF DG19 WATER TREATMENT TABLETS IN OUTDOOR CONDITIONSIn this paper, DG19 Water Treatmnent Tablets were researched and developed by the Department of Biotechnology, Joint Vietnam-Russia Tropical Science and Technology Research Centre to determine the processing threshold and effective assessment when treating water. The results showed that in the treated water sample, the initial microorganisms (E. coli < 107 CFU/mL, Total Coliform < 108 CFU/mL, Streptococci faecal < 108 CFU/mL, Pseudomonas aeruginosa < 108 CFU/mL, Spores of sulfite-reducing anaerobic bacteria < 106 CFU/mL) were not detected; heavy metals with initial concentration (Zn2+ ≤ 8 mg/L) after treatment, the obtained value less than 2 times or not detected; Permethrin insecticide from an initial concentration of ≤ 80 µg/L, after treatment with a concentration of < 15,6 µg/L or undetectable, meets the standards of QCVN 01-1:2018/BYT.These natural water sources (rivers, streams, lakes, fields) in two localities Bao Thang, Lao Cai province, and in Quang Dien district, Thua Thien Hue province, when using DG19 tablets in water treatment, the indicators as (microorganisms, turbidity, color, odor, arsenic) were lower when compared with QCVN 6-1:2010/BYT and QCVN 01-1:2018/BYT, the water after treatment was standards for use as drinking water.